DESIGN AND DEVELOPMENT OF AN ANDROID-BASED FERTILIZER ORDERING APPLICATION IN THE BANGKALA REGION - Lutvi, Lutvi Karimah; Fathahillah, Fathahillah; Sidik Sidin, Udin (Journal of Electrical Engineering and Informatics, 2024)
In the Bangkala Region of Jeneponto Regency, farmers continue to depend on the conventional system for the fertilizer ordering process. This system results in inefficiencies and consumes the time of both sellers and buyers. We require an Android-based fertilizer ordering system that integrates directly with the server. The objective of this study is to develop an Android-based application for ordering fertilizer in the Bangkala region. This application was developed using the Research and Development (R&D) methodology and the waterfall development model. The results of this research have yielded a product in the form of an Android-based fertilizer ordering application, which will be utilized by farmers in the Bangkala Region, Jeneponto Regency. The system was tested using the ISO 25010 standard across four aspects: functional suitability, portability, usability, and performance efficiency. Functional suitability testing indicates that this application is "suitable" for use. Portability testing revealed that this fertilizer ordering application system runs well on several versions of Android. The usability testing results of the application have been categorized as "Very Good". Furthermore, performance efficiency testing shows that the CPU usage is at 4%, memory usage at 156.4 Mb, and the application network activity is at 80 Kb/s. Based on this data, the application has been well-received by users and can serve as a streamlined platform for ordering fertilizers for farmers.